Argumentation and Socio-cognitive Integration in Dyadic Debates: Persuasion, Consensus, and Free Discussion in University Students - Curcio, Juan Manuel (2025)
Argumentation is a process in which reasons and justifications are produced to support a point of view. It has been widely studied due to its relationship with cognitive change and its significance in education at all levels. The present research aimed to explore three cases of university students engaged in debates across three distinct contexts (persuasion, consensus, and free debate) and their influence on the development of dialogue. The study analyzed argumentation and socio-cognitive integration, defined as the ability of students to incorporate information contributed during the debate. The findings align with previous studies but emphasize the importance of examining individual student characteristics in achieving effective socio-cognitive integration and dialogue development. Furthermore, potential theoretical and methodological implications are discussed.